Structural and biochemical remodelling in catecholamine-induced cardiomyopathy: comparative and ontogenetic aspects - Ostádal, B; Pelouch, V; Ostádalová, I; Nováková, O (Molecular and cellular biochemistry, 1995)
Excessive release or administration of beta-mimetic catecholamines may induce cardiomegaly, necrotic lesions and accumulation of connective tissue in the heart of adult homoiotherms. It was examined here whether similar changes can also be observed at different stages of evolution of the cardiovascular system, i.e. in poikilotherms and in homoiotherms during embryonic life. Sensitivity of the poikilothermic hearts (carp, frog, turtle) to isoproterenol (IPRO) was significantly lower than in the homoiotherms. Necrotic lesions, if present, were localized in the inner spongious musculature which has no vascular supply but which exhibits higher activities of enzymes connected with aerobic oxidation. Moreover, the IPRO-induced decrease of the phospholipid content was also significantly more expressed in the spongious layer. IPRO treatment did not influence the total weight of the fish heart but the proportion of the outer compact layer was significantly higher. These changes were accompanied by an increase of collagen, higher water content and an increase of isomyosin with a lower ATPase activity. The response of the poikilothermic heart to IPRO-induced overload thus differs significantly from that in the homoiotherms. The administration of IPRO during embryonic life of homoiotherms (chick) induces serious cardiovascular disturbances, including cardiomegaly and cellular oedema. Necroses of myofibrils, characteristic of IPRO-induced lesions of adults, were, however, rather exceptional. IPRO did not elevate the concentration of 85Sr (as a calcium homologue) in the immature myocardium; it seems, therefore, that IPRO-induced changes of the embryonic heart are not necessarily due to an intracellular calcium overload. It may be concluded that the character of catecholamine-induced cardiomyopathy is not uniform and depends strictly on the stage of cardiac development.
Keywords: Adrenergic beta-Agonists; kardiomyopatie; Rats; biologická evoluce; agonisté adrenergních beta-receptorů; Chick Embryo; želvy; Necrosis; kuřecí embryo; Biological Evolution; Turtles; krysa rodu Rattus; žáby; isoprenalin; myokard; zvířata; Phospholipids; Myocardium; Cardiomyopathies; Heart; nekróza; Anura; Fishes; ryby; fosfolipidy; Isoproterenol; srdce; Animals